PROGRAM USAID SEGAR UNTUK MENDUKUNG KONSERVASI HUTAN KALIMANTAN - Mewa Redo Yunia; Adiasri Putri Purbantina (Media Bina Ilmiah, 2023)
As a tropical country, Indonesia faces challenges managing forests and protected forest areas. This research discusses the degradation and deforestation of Indonesian forests, which have decreased since 2017. Problems that often arise and potentially harm Indonesia's forest ecosystems are land acquisition operations for oil palm land, mining activities, excessive excavation, shifting agriculture systems, over-exploitation of wildlife, and some prohibited activities that can disrupt the balance of an ecosystem. The United States Agency for International Development (USAID) provides funds to support the Indonesian government in various forest conservation activities under the Sustainable Environmental Governance across Regions (SEGAR). SEGAR incentivizes forest managers, farmers, and the business community to adopt sustainable production. This study employs a descriptive qualitative research method to explain the role of foreign aid in preserving forests in developing countries. The authors interview key stakeholders to explore the program's effectiveness. The study finds that SEGAR effectively promotes forest conservation in protected areas. SEGAR also increases the capacity of local community groups to manage natural resources in the area